COVID-19 Lockdown: The Impact of Home-based Training Guidance in Prevention of Football Injuries During the Return to Competition - João Miguel Ferreira Santos (2021)
Introduction: COVID-19 lockdown caused an unprecedented break in football competitions. The physiological impact in those athletes is still uncertain, and this sudden interruption can have a negative impact in injury risk during the return to competition. Accordingly, this cross-sectional study aims to assess the impact of COVID-19 lockdown in the number of injuries suffered by football players during the return to competition and to evaluate how the training adaptation and the athletes' monitoring were carried out during the lockdown. Material and Methods: An observational study was conducted and an online survey was sent to amateur and professional football players from 3 Portuguese competitions. Athletes were questioned on demographic and practice factors along with injuries suffered during the period under analysis. Results: No significant differences were found in injuries incidence between the 2020/21 (N=35) and the 2019/20 season (N=32, p=0.602). However, the absence of a training plan elaborated by the technical team for home-based trainings associated with an increased risk of injuries during the return to competition (p=0.004). Discussion: Although no significant association of this break with overall injury rate was found, it is important to maintain a continuous assessment of the players due to possible delayed lesions. Furthermore, the efforts of football teams' staff should be on the implementation of adequate training plans. Conclusion: This is the first study on COVID-19 impact on return to sports injuries in Portuguese football competitions, showing an association between these lesions and the absence of an organized training plan during the lockdown.